Navigating the Digital Shift: Unveiling the TPACK Landscape among EFL Educators in Indonesia - Sukarno; Riyadini, Maria Vineki; Alsamiri , Yasir (Script Journal: Journal of Linguistics and English Teaching, 2024)
Background: Enhancing English language learning activities can be achieved by integrating Technological Pedagogical Content Knowledge (TPACK). However, not all EFL teachers, particularly those participating in Indonesia's Teacher Professional Education Program (PPG), effectively harness TPACK to optimize their teaching methods. This study aims to explore TPACK proficiency among EFL teachers, emphasizing the disparities influenced by gender and school status, to guide targeted professional development strategies. Methodology: This study, conducted in 2023, was carried out by English Language Education study program lecturers who teach in the PPG. It employed a mixed-method study to investigate TPACK mastery among 285 EFL teachers. A comprehensive research questionnaire was developed and administered to assess TPACK proficiency, focusing on gender and school status as potential differentiators. Findings:The study delves into integrating TPACK dimensions in EFL teaching, revealing gender-neutral proficiency levels but significant disparities based on school status. While male and female teachers exhibited similar TPACK mastery, state school teachers demonstrated higher proficiency, indicating the influence of school context. Tailored professional development initiatives are crucial to address these disparities and foster effective technology integration in ELT, necessitating collaborative efforts among stakeholders to overcome challenges and promote innovative pedagogical practices conducive to modern learning environments. Conclusion:This study illuminates EFL teachers' TPACK mastery and obstacles and prospects. While ICT integration is difficult, the TPACK framework offers potential ways to create engaging learning environments. Successful implementation requires overcoming instructional challenges and maintaining stakeholder support. To maximize teaching and learning, educators must adapt their methods to technology. Originality: The study fills a knowledge gap by examining EFL teachers' TPACK proficiency, providing insights into gender and school status differences, and insights on challenges and opportunities. Given the prevalent use of technology in education, it is imperative to assess TPACK among professionally employed EFL teachers